Effects of illegal grazing and invasive Lantana camara on Asian elephant habitat use. (April 2018) - Sampson, Christie; Leimgruber, Peter; Tonkyn, David; Pastorini, Jennifer; Janaka, H.K.; Sotherden, Elaine; Fernando, Prithiviraj
Abstract: Protected areas provide some of the last refuges for Asian elephants in the wild. Managing these areas for elephants will be critical for elephant conservation. Scientists know little about elephant habitat use in Asia and how invasive species or livestock grazing influence habitat use. We studied these issues in two protected areas in Sri Lanka, Udawalawe National Park and Hurulu Eco-Park. These areas contain some of Sri Lanka's largest remaining grasslands. These grasslands are threatened by the invasive and toxic shrub, Lantana camara, and are used for illegal livestock grazing. To measure habitat use by elephants and livestock, we conducted dung surveys along over 50 km of transects stratified across grassland, scrub, and forest. We surveyed 159 vegetation plots along these transects to assess plant composition, and mapped habitat types based on satellite images. We used mixed-effect models to determine the relative importance of habitats, livestock presence, and plant associations for elephant use. Elephant presence was greatest in scrub and grassland habitats, positively associated with both livestock presence and short graminoids, and unaffected by L. camara, which was widespread but at low densities. Given the importance of these areas to elephants, we recommend a precautionary management approach that focuses on curbing both illegal grazing and the spread of L. camara . Highlights: Specific vegetation over general habitat types appear to drive elephant habitat use Elephants and livestock presence are positively correlated Low densities of the invasive Lantana camara did not deter habitat use by elephants